Modified lithium ferric manganese phosphate material, preparation method thereof and lithium ion battery

By coating the surface of the lithium iron manganese phosphate material with a hydrophobic polymer layer, the problems of increased water absorption and reduced electrical conductivity of the material are solved, and the performance of the material is improved.

CN119361691APending Publication Date: 2025-01-24ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411674689.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

After manganese doping, lithium iron manganese phosphate material has a lower conductivity and increased water absorption, which affects the processing performance and electrochemical performance of the material. The existing carbon coating modification technology cannot effectively improve its water absorption problem.

Method used

The surface of a hydrophobic polymer with a certain conductive capacity on the surface of lithium manganese manganese material is covered, forming a polymer covering layer. Specific materials include polyzide sulfe ether or its modified products, polypylene, polyiline, polyphenoli, etc. Steps such as ball grinding and baking to form modified materials.

Benefits of technology

Effectively reduce the water absorption of lithium manganese phosphate materials, while improving its conductivity, and improving the processing performance and electrochemical performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361691A_ABST
    Figure CN119361691A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a modified lithium ferric manganese phosphate material, a preparation method thereof and a lithium ion battery. The modified lithium ferric manganese phosphate material comprises a lithium ferric manganese phosphate nuclear layer and a polymer coating layer coating the surface of the lithium ferric manganese phosphate nuclear layer, the material of the polymer coating layer comprises at least one of modified polyphenylene sulfide or a modified product thereof, polypyrrole, polyaniline and polythiophene; the material of the polymer coating layer is (CxHySaNbBcFd) n, wherein 2 < = x < = 8, 0 < = y < = 8, 0 < = a < = 2, 0 < = b < = 2, 0 < = c < = 0.5, 0 < = d < = 0.5, and n > = 10; the surface of the lithium ferric manganese phosphate material is coated with the hydrophobic material with conductivity to form a polymer coating layer, so that the water absorption of the lithium ferric manganese phosphate material can be reduced, the conductivity of the lithium ferric manganese phosphate material can be improved, and the processability and electrochemical performance of the lithium ferric manganese phosphate material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a modified lithium iron manganese phosphate material, a preparation method thereof, and a lithium ion battery. Background Art

[0002] As one of the core elements of lithium-ion batteries, positive electrode materials directly affect their performance, cost, life and safety. Among many commercial positive electrode materials, lithium iron phosphate has lower cost and good safety performance. The industrial production process of lithium iron phosphate positive electrode materials is already very mature, and the prepared positive electrode materials can obtain a specific capacity close to the theoretical value during the charge and discharge process at a lower current density. After lithium iron phosphate is doped with manganese, the resulting lithium iron manganese phosphate material exhibits a higher operating voltage. Therefore, lithium iron manganese phosphate material has also become one of the research hotspots in recent years.

[0003] However, the addition of manganese also brings certain side effects, which reduces the conductivity of lithium iron manganese phosphate materials and increases their water absorption. Water will react with the lithium iron manganese phosphate material and generate alkaline substances such as lithium hydroxide and lithium carbonate on the surface, thereby affecting the overall processing performance and electrical properties of the material; when lithium iron manganese phosphate is used as a positive electrode material for batteries, the water in the lithium iron manganese phosphate will also react with the electrolyte to produce hydrofluoric acid, causing manganese to dissolve out of the lithium iron manganese phosphate material, directly affecting battery performance; usually, the industry uses carbon coating technology to construct a conductive network on the surface of lithium iron manganese phosphate materials to improve their conductivity; however, the current existing carbon coating modification technology still cannot improve the water absorption problem of lithium iron manganese phosphate materials. Summary of the invention

[0004] In view of the above problems existing in the prior art, the object of the present invention is to provide a modified lithium iron manganese phosphate material and a preparation method thereof and a lithium ion battery.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a modified lithium iron manganese phosphate material, comprising a lithium iron manganese phosphate core layer and a polymer coating layer coated on the surface of the lithium iron manganese phosphate core layer;

[0007] The material of the polymer coating layer includes at least one of polyphenylene sulfide or its modified product, polypyrrole, polyaniline, and polythiophene; and the material of the polymer coating layer is (C x H y S a N b B c F d ) n , where 2≤x≤8, 0≤y≤8, 0≤a≤2, 0≤b≤2, 0≤c≤0.5, 0≤d≤0.5, n≥10.

[0008] In some embodiments, the thickness of the polymer coating layer is 0.5-2.5 nm; the particle size of the lithium iron manganese phosphate core layer is 0.1-10 um.

[0009] In some embodiments, the ratio of the thickness of the polymer coating layer to the particle size of the lithium iron manganese phosphate core layer is 0.00025:1 to 0.025:1.

[0010] In some embodiments, the material of the polymer coating layer is modified polyphenylene sulfide, and the mass of the modified polyphenylene sulfide accounts for 0.01 to 1% of the mass of the lithium iron manganese phosphate core layer; wherein the chemical formula of the modified polyphenylene sulfide is (C 6 H 3.6 SB 0.1 F 0.1 )n.

[0011] In some embodiments, the contact angle of the material of the polymer coating layer is 110° to 150°; the conductivity of the material of the polymer coating layer is 1×10 -7 ~1×10 -3 S / cm.

[0012] The present invention also provides a method for preparing a modified lithium iron manganese phosphate material, comprising the following steps:

[0013] preparing a lithium iron manganese phosphate material to obtain a lithium iron manganese phosphate core layer;

[0014] A polymer material is coated on the lithium iron manganese phosphate core layer to form a polymer coating layer to obtain a modified lithium iron manganese phosphate material; the polymer material includes at least one of polyphenylene sulfide or its modified product, polypyrrole, polyaniline, and polythiophene; and the material of the polymer coating layer is (C x H y S a N b B c F d ) n , where 2≤x≤8, 0≤y≤8, 0≤a≤2, 0≤b≤2, 0≤c≤0.5, 0≤d≤0.5, n≥10.

[0015] In some embodiments, the step of coating the lithium iron manganese phosphate core layer with a polymer material to obtain a modified lithium iron manganese phosphate material comprises:

[0016] The lithium iron manganese phosphate material and the polymer material are fully mixed by ball milling, and then heated and baked in a nitrogen atmosphere. After cooling, the mixture is ground in an inert atmosphere to obtain a modified lithium iron manganese phosphate material.

[0017] In some embodiments, the temperature of the temperature-raising baking is 100-400° C., the rate of the temperature-raising baking is 1-5° C. / min, and the time of the temperature-raising baking is 2-10 h.

[0018] In some embodiments, the method for preparing the lithium iron manganese phosphate material comprises:

[0019] A lithium source, an iron source, a manganese source and a phosphorus source are mixed, and lithium iron manganese phosphate material is obtained through a high-temperature solid phase synthesis reaction.

[0020] The present invention further provides a lithium-ion battery, comprising a positive electrode, wherein the material of the positive electrode comprises the modified lithium iron manganese phosphate material or the modified lithium iron manganese phosphate material prepared according to the preparation method of the modified lithium iron manganese phosphate material.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention coats a hydrophobic material with a certain electrical conductivity on the surface of the lithium iron manganese phosphate material to form a polymer coating layer, which can effectively reduce the water absorption of the lithium iron manganese phosphate material and improve the electrical conductivity of the lithium iron manganese phosphate material. The present invention is beneficial to improving the processing performance of the lithium iron manganese phosphate material and effectively improving the electrochemical properties of the lithium iron manganese phosphate material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a SEM image of the lithium iron manganese phosphate material coated with modified polyphenylene sulfide in Example 1 of the present invention;

[0024] Figure 2 It is a SEM image of the thickness of the modified polyphenylene sulfide coating layer in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.

[0026] Example 1

[0027] This embodiment 1 provides a modified lithium iron manganese phosphate material. The preparation steps of the modified lithium iron manganese phosphate material are as follows:

[0028] Step 1: A lithium source, an iron source, a manganese source, and a phosphorus source are synthesized by a high temperature solid phase method according to a stoichiometric ratio of Li:Fe:Mn:P=1.1:0.6:0.4:1 to obtain a lithium iron manganese phosphate raw material;

[0029] Step 2: Synthesize polyphenylene sulfide using p-dichlorobenzene and sodium sulfate, add polyphenylene sulfide into a boron trifluoride solution to prepare modified polyphenylene sulfide, the chemical formula of the modified polyphenylene sulfide is (C6 H 3.6 SB 0.1 F 0.1 ) n ;

[0030] Step 3: The lithium iron manganese phosphate raw material and the modified polyphenylene sulfide are fully mixed by ball milling, and the temperature is increased to 250° C. at a heating rate of 1 to 5° C. / min in a nitrogen atmosphere, and baked at 250° C. for 6 hours to obtain a mixture, and after the mixture is cooled, it is placed in an inert atmosphere for grinding, and after the grinding is completed, a modified lithium iron manganese phosphate material with a lithium iron manganese phosphate core layer coated with modified polyphenylene sulfide as a polymer coating layer is obtained;

[0031] Among them, the thickness of the polymer coating layer is 1.5nm, the particle size of the lithium iron manganese phosphate core layer is 1um, and the ratio of the thickness of the polymer coating layer to the particle size of the lithium iron manganese phosphate core layer is 0.015:1; based on the mass of the lithium iron manganese phosphate raw material as 100%, the amount of modified polyphenylene sulfide added is 0.5%.

[0032] Embodiment 2-7

[0033] Specifically, Examples 2-7 all provide a modified lithium iron manganese phosphate material;

[0034] The only difference between Example 2 and Example 1 is that the amount of modified polyphenylene sulfide used is 0.01%; in the modified lithium iron manganese phosphate material obtained in Example 2, the thickness of the polymer coating layer is 0.5nm; the particle size of the lithium iron manganese phosphate core layer is 1um, and the ratio of the thickness of the polymer coating layer to the particle size of the lithium iron manganese phosphate core layer is 0.005:1.

[0035] The only difference between Example 3 and Example 1 is that the amount of modified polyphenylene sulfide used is 1.0%; in the modified lithium iron manganese phosphate material obtained in Example 3, the thickness of the polymer coating layer is 2.5nm; the particle size of the lithium iron manganese phosphate core layer is 1um, and the ratio of the thickness of the polymer coating layer to the particle size of the lithium iron manganese phosphate core layer is 0.025:1.

[0036] The only difference between Example 4 and Example 1 is that the baking is carried out at 100°C for 6 hours under a nitrogen atmosphere; in the modified lithium iron manganese phosphate material obtained in Example 4, the thickness of the polymer coating layer is 1.8 nm; the particle size of the lithium iron manganese phosphate core layer is 1 um, and the ratio of the thickness of the polymer coating layer to the particle size of the lithium iron manganese phosphate core layer is 0.018:1.

[0037] The only difference between Example 5 and Example 1 is that the baking is carried out at 400°C for 6 hours under a nitrogen atmosphere; in the modified lithium iron manganese phosphate material obtained in Example 2, the thickness of the polymer coating layer is 1.1 nm; the particle size of the lithium iron manganese phosphate core layer is 1 um, and the ratio of the thickness of the polymer coating layer to the particle size of the lithium iron manganese phosphate core layer is 0.011:1.

[0038] The only difference between Example 6 and Example 1 is that in step 3, the lithium iron manganese phosphate material raw material and the modified polyphenylene sulfide are directly mixed by ball milling to obtain a modified lithium iron manganese phosphate material with modified polyphenylene sulfide as a polymer coating layer to coat the lithium iron manganese phosphate core layer; wherein the thickness of the polymer coating layer is 2.1nm; the particle size of the lithium iron manganese phosphate core layer is 1um, and the ratio of the thickness of the polymer coating layer to the particle size of the lithium iron manganese phosphate core layer is 0.021:1.

[0039] The only difference between Example 7 and Example 1 is that in step 2, p-dichlorobenzene and sodium sulfate are used to synthesize polyphenylene sulfide; in step 3, the modified polyphenylene sulfide is replaced by polyphenylene sulfide; in the modified lithium iron manganese phosphate material obtained in Example 7, the thickness of the polymer coating layer is 1.3nm; the particle size of the lithium iron manganese phosphate core layer is 1um, and the ratio of the thickness of the polymer coating layer to the particle size of the lithium iron manganese phosphate core layer is 0.013:1.

[0040] Comparative Example 1

[0041] Comparative Example 1 provides a lithium iron manganese phosphate material; the preparation steps of the lithium iron manganese phosphate material are as follows:

[0042] A lithium source, an iron source, a manganese source, and a phosphorus source are synthesized by a high temperature solid phase method according to a stoichiometric ratio of Li:Fe:Mn:P=1.1:0.6:0.4:1 to obtain a lithium iron manganese phosphate raw material;

[0043] The lithium iron manganese phosphate raw material is heated to 250° C. at a heating rate of 1 to 5° C. / min under a nitrogen atmosphere, and baked at 250° C. for 6 hours. After cooling, it is placed in an inert atmosphere for grinding, and after grinding, the lithium iron manganese phosphate material is obtained.

[0044] Comparative Example 2

[0045] Comparative Example 2 provides a lithium iron manganese phosphate material; the preparation steps of the lithium iron manganese phosphate material are as follows:

[0046] A lithium source, an iron source, a manganese source, and a phosphorus source are synthesized by a high temperature solid phase method according to a stoichiometric ratio of Li:Fe:Mn:P=1.1:0.6:0.4:1 to generate a lithium iron manganese phosphate raw material;

[0047] The lithium iron manganese phosphate raw material and the carbon source are fully mixed by ball milling, heated to 1000° C. at a heating rate of 5 to 10° C. / min in a nitrogen atmosphere, and calcined at 1000° C. for 12 to 24 hours. After cooling, the raw material is placed in an inert atmosphere for grinding to obtain the lithium iron manganese phosphate material.

[0048] The carbon source includes but is not limited to glucose, sucrose, polyethylene glycol and acetylene black; based on the mass of the lithium iron manganese phosphate raw material being 100%, the amount of the added carbon source is 0.5%.

[0049] Test Case

[0050] The lithium iron manganese phosphate materials prepared in Examples 1 to 7 and Comparative Examples 1 and 2 were assembled to obtain lithium ion button batteries, and the lithium ion batteries were tested for electrical performance at room temperature, with a charge and discharge condition of 0.05C and a charge and discharge range of 2.0V-4.35V; the test electrical performance results are shown in Table 1;

[0051] Table 1

[0052]

[0053] The conductivity of the lithium iron manganese phosphate materials prepared in Examples 1 to 7 and Comparative Examples 1 and 2 was tested, and the test results are shown in Table 2;

[0054] Table 2

[0055]

[0056] The contact angle test was performed on the lithium iron manganese phosphate materials prepared in Examples 1 to 7 and Comparative Examples 1 and 2. The test results are shown in Table 3;

[0057] Table 3

[0058]

[0059] The lithium iron manganese phosphate material prepared in Example 1 was observed using a scanning electron microscope; Figure 1 This is the SEM image of the modified polyphenylene sulfide coated lithium iron manganese phosphate raw material. Figure 2 SEM image of the thickness of the modified polyphenylene sulfide coating layer.

[0060] Example 1 is a preferred embodiment provided by the present invention. Compared with Example 1, the amount of modified polyphenylene sulfide is adjusted in Examples 2 and 3. In Comparative Example 1, the polymer coating layer is not coated on the surface of the lithium iron manganese phosphate raw material. In Comparative Example 2, a carbon source is used instead of modified polyphenylene sulfide to coat the lithium iron manganese phosphate raw material. Combining the data in Tables 1 to 3, it can be seen that in Examples 1, 2 and 3, the conductivity and contact angle data of the modified lithium iron manganese phosphate material obtained when the amount of modified polyphenylene sulfide is 0.5% are better, and the prepared lithium ion battery has better performance; and the test results of Examples 1, 2 and 3 are better than the test results of the lithium iron manganese phosphate materials obtained in Comparative Examples 1 and 2; further confirming the superiority of the method of using modified polyphenylene sulfide to coat the lithium iron manganese phosphate raw material in the present invention, the polymer coating layer obtained on the surface of the lithium iron manganese phosphate can effectively reduce its water absorption, while improving the conductivity of the lithium iron manganese phosphate, which is beneficial to improving the performance of the lithium ion battery.

[0061] Combined with the data in Table 1, it can be seen that in Example 1, Example 4 and Example 5, when the baking temperature is within 100°C to 400°C, the discharge gram capacity and capacity retention rate of the lithium ion batteries prepared in Example 1, Example 4 and Example 5 are better than those in Comparative Example 1 and Comparative Example 2, and the performance of the lithium ion battery prepared when the baking temperature is 250°C is better; when carbon-coated lithium iron manganese phosphate is used in Comparative Example 2, high temperature calcination at 1000°C is required for 12h to 24h; while in this scheme, the steps of baking at 100 to 400°C under a nitrogen atmosphere for 2h to 10h, and grinding in an inert atmosphere after cooling, are not only beneficial to improve The modified polyphenylene sulfide is evenly coated on the surface of the lithium iron manganese phosphate material, and the process is simpler and the energy consumption is reduced. In addition, compared with Example 1, the baking step in step 3 is not performed in Example 6, and the lithium iron manganese phosphate material raw material and the modified polyphenylene sulfide are directly mixed by ball milling to form a coating layer. Combined with the data in Table 1, it can be seen that the lithium ion battery prepared in Example 6 has lower performance than that in Example 1 in terms of discharge gram capacity and capacity retention rate. This further illustrates the superiority of the method of mixing the lithium iron manganese phosphate raw material and the modified polyphenylene sulfide by ball milling and then baking them at 100°C to 400°C in a nitrogen atmosphere for 2h to 10h in this scheme.

[0062] Compared with Example 1, polyphenylene sulfide is used instead of modified polyphenylene sulfide to coat lithium iron manganese phosphate in Example 7; combined with the data in Tables 1 to 3, it can be seen that the lithium ion battery prepared in Example 7 is better than Comparative Examples 1 and 2 in performance such as capacity retention rate, but lower than the data of Example 1; it shows that the use of modified polyphenylene sulfide to coat lithium iron manganese phosphate can obtain lithium iron manganese phosphate materials with better conductivity and better electrochemical properties.

[0063] Combining the data in Tables 1 to 3, it can be seen that the modified lithium iron manganese phosphate materials obtained in Examples 1 to 7 are better than those in Comparative Examples 1 and 2 in terms of conductivity and contact angle, which shows that the material performance obtained by the scheme of using a polymer coating layer to coat the lithium iron manganese phosphate in the present invention is better than the performance of the uncoated lithium iron manganese phosphate material and the material performance of the carbon-coated lithium iron manganese phosphate.

[0064] The above are only partial or preferred embodiments of the present invention. Neither the text nor the drawings can limit the scope of protection of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the overall concept of the present invention, or direct / indirect application in other related technical fields are included in the scope of protection of the present invention.

Claims

1. A modified lithium iron manganese phosphate material, characterized in that: It comprises a lithium iron manganese phosphate core layer and a polymer coating layer coated on the surface of the lithium iron manganese phosphate core layer; The material of the polymer coating layer includes at least one of polyphenylene sulfide or its modified product, polypyrrole, polyaniline, and polythiophene; and the material of the polymer coating layer is (C x H y S a N b B c F d ) n , where 2≤x≤8, 0≤y≤8, 0≤a≤2, 0≤b≤2, 0≤c≤0.5, 0≤d≤0.5, n≥10.

2. The modified lithium iron manganese phosphate material according to claim 1, characterized in that: The thickness of the polymer coating layer is 0.5-2.5 nm; the particle size of the lithium iron manganese phosphate core layer is 0.1-10 um.

3. The modified lithium iron manganese phosphate material according to claim 1, characterized in that: The ratio of the thickness of the polymer coating layer to the particle size of the lithium iron manganese phosphate core layer is (0.00025-0.025):

1.

4. The modified lithium iron manganese phosphate material according to claim 1, characterized in that: The material of the polymer coating layer is modified polyphenylene sulfide, and the mass of the modified polyphenylene sulfide accounts for 0.01-1% of the mass of the lithium iron manganese phosphate core layer.

5. The modified lithium iron manganese phosphate material according to claim 1, characterized in that: The contact angle of the material of the polymer coating layer is 110° to 150°; and / or the conductivity of the material of the polymer coating layer is 1×10 -7 ~1×10 -3 S / cm.

6. A method for preparing a modified lithium iron manganese phosphate material, characterized in that: The steps include: preparing a lithium iron manganese phosphate material to obtain a lithium iron manganese phosphate core layer; A polymer material is coated on the lithium iron manganese phosphate core layer to form a polymer coating layer to obtain a modified lithium iron manganese phosphate material; the polymer material includes at least one of polyphenylene sulfide or its modified product, polypyrrole, polyaniline, and polythiophene; and the material of the polymer coating layer is (C x H y S a N b B c F d ) n , where 2≤x≤8, 0≤y≤8, 0≤a≤2, 0≤b≤2, 0≤c≤0.5, 0≤d≤0.5, n≥10.

7. The method for preparing the modified lithium iron manganese phosphate material according to claim 6, characterized in that: The step of coating the lithium iron manganese phosphate core layer with a polymer material to obtain a modified lithium iron manganese phosphate material comprises: The lithium iron manganese phosphate material and the polymer material are fully mixed by ball milling, and then heated and baked in a nitrogen atmosphere. After cooling, the material is ground in an inert atmosphere to obtain a modified lithium iron manganese phosphate material.

8. The method for preparing the modified lithium iron manganese phosphate material according to claim 7, characterized in that: The temperature of the heating and baking is 100-400° C., the rate of the heating and baking is 1-5° C. / min, and the time of the heating and baking is 2-10 hours.

9. The method for preparing the modified lithium iron manganese phosphate material according to claim 8, characterized in that: The preparation method of the lithium iron manganese phosphate material comprises: A lithium source, an iron source, a manganese source and a phosphorus source are mixed, and lithium iron manganese phosphate material is obtained through a high-temperature solid phase synthesis reaction.

10. A lithium ion battery, characterized in that: It comprises a positive electrode, wherein the material of the positive electrode comprises the modified lithium iron manganese phosphate material according to any one of claims 1 to 4 or the modified lithium iron manganese phosphate material prepared according to the preparation method of the modified lithium iron manganese phosphate material according to any one of claims 5 to 8.

Citation Information

Patent Citations

  • Positive electrode active substance and preparation method thereof, positive electrode material containing positive electrode active substance and battery

    CN105810940A

  • Composite current collector, composite electrode sheet comprising composite current collector and electrochemical device

    CN109994740A

  • Oxide positive electrode material coated with conductive polymer through ball milling and preparation method and application of oxide positive electrode material

    CN114361395A

  • Conductive polymer in-situ coated lithium iron manganese phosphate / carbon positive electrode material and preparation method thereof

    CN117038930A

  • Polyphenylene sulfide (PER)fluoropolymer materials and process for preparation and use therof

    US20110040017A1